2018
DOI: 10.3171/2018.9.focus18369
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury among female veterans: a review of sex differences in military neurosurgery

Abstract: The impact of traumatic brain injury (TBI) has been demonstrated in various studies with respect to prevalence, morbidity, and mortality data. Many of the patients burdened with long-term sequelae of TBI are veterans. Although fewer in number, female veterans with TBI have been suggested to suffer from unique physical, mental, and social challenges. However, there remains a significant knowledge gap in the sex differences in TBI. Increased female representation in the military heralds an increased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Research demonstrates that rates of TBI are higher for men than women in both veteran (Morissette et al., 2011 ) and civilian populations (Bruns & Hauser, 2003 ; Frost et al., 2013 ; Mollayeva et al., 2018 ). Despite higher rates of TBI among men, women with deployment‐related mild TBI typically report more neurobehavioral symptoms than men, such as higher levels of depressive symptom severity and suicidality (Amoroso & Iverson, 2017 ; Cogan et al., 2019; Epstein et al., 2019 ; Farace & Alves, 2000 ; Hoge et al., 2008 ; Iverson et al., 2011 ; Kim et al., 2018 ).…”
mentioning
confidence: 99%
“…Research demonstrates that rates of TBI are higher for men than women in both veteran (Morissette et al., 2011 ) and civilian populations (Bruns & Hauser, 2003 ; Frost et al., 2013 ; Mollayeva et al., 2018 ). Despite higher rates of TBI among men, women with deployment‐related mild TBI typically report more neurobehavioral symptoms than men, such as higher levels of depressive symptom severity and suicidality (Amoroso & Iverson, 2017 ; Cogan et al., 2019; Epstein et al., 2019 ; Farace & Alves, 2000 ; Hoge et al., 2008 ; Iverson et al., 2011 ; Kim et al., 2018 ).…”
mentioning
confidence: 99%
“…It is well established in the literature that service women and released or retired women Veterans face distinct sex-and gender-specific risks for injuries and illnesses. 13 The reviewed research on women Veterans covers a long list of concerns: posttraumatic stress disorder (PTSD), 38,39 depression, 40,41 selfharm and suicide, 42,43 eating disorders, 44,45 insomnia, 46,47 chronic pain conditions, 48,49 reproductive health, 50,51 sexual health, 52,53 traumatic brain injuries, 54,55 musculoskeletal conditions, 56,57 cardiovascular conditions, 58,59 irritable bowel syndrome, 60 cancer, 61,62 diabetes, 63,64 and more. Increasingly, the research recognizes the complex multi-factorial nature of women Veterans' health challenges by addressing correlates between mental and physical health conditions and delineating links to military-related factors.…”
Section: Challenges Faced By Women and Other Historically Under-represented Veteransmentioning
confidence: 99%
“…A systematic review of veteran patients with TBI showed that, compared with men, women were less likely to suffer from TBI, and the incidence of emergency craniectomy was also lower. However, data regarding the incidence difference of long-term post TBI syndrome in male and female service members are still inadequate [16].…”
Section: Introductionmentioning
confidence: 99%